メタボリックシンドロームにおける血管周囲脂肪組織による血管弛緩反応の増強作用消失のメカニズム - 籠田, 智美; 篠塚, 和正; 麓（丸山）, 加菜; 懐, 理紗 (日本薬理学会年会要旨集, 2022)
Sex differences in the modulatory function of arterial tone by perivascular adipose tissue (PVAT) are reported. We demonstrated that sex difference in enhancing vasorelaxation response by PVAT in renal arteries differs between metabolic syndrome (MetS) model strains, SHRSP.Z-Leprfa/IzmDmcr rats (SPZF) and SHR/NDmcr-cp rats (CP), at the same age. The underlying mechanism of this discrepancy was investigated.Systolic blood pressure (sBP) was measured using a tail-cuff method. Ring preparations with and without PVAT were made from male and female SPZF and CP renal arteries at 23 weeks of age. Vasorelaxation and mRNA transcript levels in PVAT were examined using organ bath methods and quantitative real-time polymerase chain reaction, respectively.sBP was higher in SPZF than CP but lower in females than males. PVAT increased acetylcholine-induced relaxations in renal arteries in CP females only. There were no significant differences in mRNA levels of angiotensin II type 1 receptor (AT1R) and AT1R-associated protein (ATRAP) among groups, but the AT1R/ATRAP ratio, which indicates AT1R activity, was lower in CP than SPZF. The AT1R/ATRAP ratio in PVAT was negatively correlated with enhancing the effects of PVAT on acetylcholine-induced relaxations while positively correlated with sBP.This study suggests that overactivation of AT1R signaling in PVAT, probably resulting from high blood pressure, induces the decline in compensatory PVAT effects in MetS. Negative regulation of AT1R signaling is beneficial for sustained favorable PVAT effects.